Die griechischen und jüdischen Gründungslegenden Alexandrias - Schwemer, Anna Maria (Biblische Notizen, 2011)
Like their pagan neighbours, whose legends survived mainly in the Alexander romance, the Jews of Alexandria glorified the early history of their hometown. They too told stories about Alexander the Great, but they replaced the pagan traditions about Agathos Daimon and snake cult with the legends about Jeremiah and Alexander.